DETERMINATION OF ORGANOCHLORINE PESTICIDES IN DRINKING WATERS SAMPLED FROM CLUJ AND HUNEDOARA COUNTIES - MARIA-ELISABETA LOVÁSZ; IRINA DUMITRAŞCU; OVIDIU TRAIAN POPA; ANCA ELENA GURZĂU (Aerul şi Apa: Componente ale Mediului, 2011)
Determination of organochlorine pesticides in drinking waterssampled from Cluj and Hunedoara counties. Pesticides are found scattered indifferent environmental factors (water, air, soil) wherefrom they are drawn off byvegetal and animal organisms. Water pollution by pesticides results from the plantprotection products industry and also from massive application of these resourcesin agriculture and other branches of economy. Pesticides can reach surface wateralong with dripping waters and by infiltration may reach the groundwater layers,organochlorine pesticides are most often found in the water sources (dieldrin,endrin, DDT, aldrin, lindane, heptachlor, etc.) due to their increased persistence inthe external environment. This study followed up the determination oforganochlorine pesticides in 14 drinking water samples collected from the outputof water treatment plants in Cluj and Hunedoara counties that process surfacewater and deep-water sources. For identification of organochlorine pesticides, thegas chromatographic method after liquid-liquid extraction was used, by a gascromatograph Shimadzu GC 2010 with detector ECD (Electron CaptureDetection). There were not detected higher values than the method detection limit(0.01 μg/l) in the drinking water samples collected and analyzed for both totalorganochlorine pesticides and components, which were well below the maximumconcentration admitted by Law 452/2002 regarding drinking water quality. Resultsare correlated with the sanitary protection areas for water sources and with the useof agricultural lands in the area. The solution to reduce risk of pesticides use isecological agriculture , which gains increasingly more ground in Romania too.